ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA BERPRESTASI KELAS X DAN XI DI SMA NEGERI 8 PEKANBARU - Rukmana, Isna Sari; ', Gimin; ', Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was inspired by the amount of outstanding students of SMA Negeri 8 Pekanbaru,their motivation in learning would be undeniably different from other students, the researchers then interested in knowing how their learning motivation brings a skillful performance in numerous field of sciences. The study was formulatedon how is exemplary students’ learning motivation at grade X and XI? and what factors do influence their learning motivation? This study wasa descriptive quantitative. The instrument for the data collection was a questionnaire which consist of 34 statements. The result statistically showed that their motivation is high by 95%. Meanwhile, there were six factors that influenced their learning motivation (1) student’s aspiration 0,291, (2) student’s ability 1,280, (3) student’s condition 0,525, (4) students' environment 0,281, (5) dynamic elements in teaching and learning 0,562, and (6) teachers’ efforts in teaching 0.573. Therefore, the hypothesis that stated